2013
DOI: 10.1016/j.psychres.2012.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and mental imagery: A possible cognitive marker to promote well-being?

Abstract: Optimism is associated with a range of benefits not only for general well-being, but also for mental and physical health. The development of psychological interventions to boost optimism derived from cognitive science would have the potential to provide significant public health benefits, yet cognitive markers of optimism are little understood. The current study aimed to take a first step in this direction by identifying a cognitive marker for optimism that could provide a modifiable target for innovative inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
113
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 37 publications
19
113
0
4
Order By: Relevance
“…In order to establish a causal relation optimism needs to be manipulated experimentally. It has been shown previously that the vividness of positive mental imagery of the future is associated with optimism, suggesting that imagery exercises are a powerful way to increase optimism and thereby mental wellbeing (Blackwell et al, 2013). In line with this, previous experimental studies that used imagery exercises to induce optimism found that imagery of positive future events indeed increased optimism and positive mood ratings (Sheldon and Lyubomirsky, 2006;Peters et al, 2010;Meevissen et al, 2011).…”
Section: Introductionsupporting
confidence: 60%
“…In order to establish a causal relation optimism needs to be manipulated experimentally. It has been shown previously that the vividness of positive mental imagery of the future is associated with optimism, suggesting that imagery exercises are a powerful way to increase optimism and thereby mental wellbeing (Blackwell et al, 2013). In line with this, previous experimental studies that used imagery exercises to induce optimism found that imagery of positive future events indeed increased optimism and positive mood ratings (Sheldon and Lyubomirsky, 2006;Peters et al, 2010;Meevissen et al, 2011).…”
Section: Introductionsupporting
confidence: 60%
“…Other studies found no association between dispositional optimism and judgements of negative events, such as perceiving the risk of heart attack, obesity or severe acute respiratory syndrome on samples of adults (e.g., Geers et al, 2013;Radcliffe & Klein, 2002) and undergraduate students (e.g., Ji, Zhang, Usborne, & Guan, 2004). Moreover, previous literature consistently showed that adults with a high level of dispositional optimism were more likely to expect more positive events to happen to them in the future (e.g., Blackwell et al, 2013;Sharot, Riccardi, Raio, & Phelps, 2007).…”
Section: Dispositional Optimismmentioning
confidence: 95%
“…El optimismo disposicional se ha asociado con una buena percepción de apoyo social [10], con la generación de imágenes más vívidas sobre los eventos positivos que se quieren experimentar [11] y puede ayudar a proteger al individuo de la ansiedad y la depresión en momentos en que el logro no es alcanzado [12]. En una revisión sistemática [8] algunos hallazgos resaltan la importancia del optimismo cuando se padecen enfermedades crónicas: bajos niveles de ansiedad y depresión a través de los seguimientos en pacientes con cáncer de mama, influencia indirecta en comportamientos relacionados con la salud en pacientes con problemas cardiovasculares, reducción en la incidencia de enfermedad coronaria en mujeres y promoción del bienestar subjetivo y de comportamientos protectores.…”
Section: Optimismo Disposicionalunclassified